Analisis Kelayakan Usaha Warung Kopi Di Kelurahan Nginden Jangkungan Kecamatan Sukolilo Kota Surabaya - Stefanus Jenarut; Kunto Inggit Gunawan (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
The coffee shop business in Nginden Jangkungan Village, Sukolilo District, Surabaya City, was studied by 6 people and the average income generated was IDR 20,195,000 / month, and had an average total cost incurred each month, namely IDR 8,386,032 / month. For the average profit that will be obtained from the 6 coffee shop business owners studied in the Keputih Village, Sukolilo District, Surabaya City, it is IDR 11,808,967/month. Furthermore, the lowest profit was obtained by Mr. Ridwan, the owner of the Giras Panorama coffee shop, amounting to Rp. 8,460,561/month and the highest was obtained by Mr. Arifudin, amounting to Rp. 16,561,839/month. Meanwhile, Mr. Ridwan is the owner of the largest business capital, namely Rp. 20,249,439/month and the smallest is Mr. Fauzi, which is Rp. 3,802,944. /month. Meanwhile with regard to ROI, the lowest percentage was obtained from the Giras Panorama coffee shop business of 41,781% and the highest was the NS 58 coffee shop, namely 393,827%. the average ROI value of the six coffee shops is 196,290%. In simple terms, in 1 year the average rate of return on investment for the six coffee shops studied was 196,290%. For R/C calculations, the largest value was obtained from the NS 58 coffee shop with 4,938 and the smallest was the Giras Panorama coffee shop with 1,417. The average R/C value for the six coffee shops is 2,962.5. That is, with a capital of IDR 1,000, coffee shops on average earn IDR 2,962.5 or get a profit of IDR 1,962.5 because the total income of the six coffee shops is far greater than the total monthly costs. For the calculation of the B/C ratio, the largest value was obtained for the NS 58 coffee shop at 3,938 and the smallest was for the Giras Panorama coffee shop at 0,417. Meanwhile, the average value of the B/C ratio for the six coffee shops was 1,962.5. That is, Mr. Ridwan as the owner of the Giras Panorama coffee shop which has a ratio of 0.417 or it can be said that it is not feasible to run.